Foundation flash catalyst - Goralski, Greg (Friends of ED Adobe learning library., 2010)
This book offers an introduction to Flash Catalyst for designers with intermediate to advanced skills. It discusses where Catalyst sits within the production process and how it communicates with other programs. It covers all of the features of the Flash Catalyst workspace, teaching you how to create designs from scratch, how to build application designs and add functionality, and how to master the Catalyst/Flex workflow. * Introduces Flash Catalyst * Focuses on production process * Covers the interrelation between Flash Catalyst and Photoshop/Illustrator/Flex/Flash What you'll learn Starting f.